Gendered perspectives on women's anabolic-androgenic steroid (AAS) usage practices - Tim Piatkowski; Jonathan Robertson; Severine Lamon; Matthew Dunn (BMC, 2023)
Abstract Background The masculinizing effects from anabolic-androgenic steroid (AAS) appear to be different between men and women, leading to calls for more gender-specific information regarding women and AAS use. This study sought to gather perspectives from both men and women on the unique challenges surrounding women's use of AAS, irrespective of their personal use. Secondly, the study interrogated how women's AAS practices differ from those of men specifically. Methods The data presented in this paper come from a subsample of participants who participated in a larger study investigating women and performance and image enhancing drug (PIED) use in Australia. Participants were included in the current analysis if they were: (i) males or females who competed with or coached female strength athletes using AAS and (ii) female and male strength athletes who used AAS. The final sample comprised 21 participants of which there was a proportion of males (n = 7) and females (n = 7) using AAS. Results Women's choices in AAS selection were predominantly around oral compounds (e.g. Oxandrolone) as well as other PIEDs (e.g. Clenbuterol). Some women report the use of injectable AAS represents a change in the profile of the typical female user as it reportedly comes alongside drastic physical and psychological changes. Conclusions The unique challenges facing women who use AAS are largely isolation and stigma, with little evidence-based practice or education being available to them online or through peer-groups. Future work may consider piloting harm reduction strategies that may be co-designed with this group.